Foreword - GURGU, Elena (Annals of Spiru Haret University. Economic Series, 2018)
A globally warning issued in September 2018 by the former president of the European Central Bank, Frenchman Jean-Claude Trichet says the world economy is exactly the way ahead of the economic crisis of 2008. He said that too many debts have done the global financial system as vulnerable as it was ten years ago in September 2008, when the American bank Lehman Brothers collapsed. Excessive indebtedness in advanced economies was a key factor in triggering the global financial crisis of 2007 and 2008, Jean-Claude Trichet said in an interview with AFP. Currently, debt growth in advanced countries, particularly in the private sector, has slowed, but this slowdown has been offset by an acceleration in emerging-nation debt growth. This makes the entire world financial system at least the same vulnerable as it was in 2008......